Dietary change in Cape gannets reflects distributional and demographic shifts in two South African commercial fish stocks. (23rd November 2014) - Green, David B.; Klages, Norbert T. W.; Crawford, Robert J. M.; Coetzee, Janet C.; Dyer, Bruce M.; Rishworth, Gavin M.; Pistorius, Pierre A.
Abstract: Seabirds are upper trophic level predators, and are often highly sensitive to changes in the availability of their prey. Altered prey assemblages resulting from fluctuations in oceanographic conditions may be mirrored by shifts in seabird diet. Long-term studies of dietary change in seabirds therefore provide valuable insight into the nature of environmental shifts within the systems in which they forage. In recent decades, the Agulhas region in South Africa has undergone significant oceanographic change related to warming and intensification of the Agulhas current. Concurrent with this change, the population of Cape gannets Morus capensis at Bird Island, Algoa Bay, has grown rapidly, probably as a result of an increased availability of its dominant prey items, sardine Sardinops sagax and anchovy Engraulis encrasicolus . Using one of the longest and most complete time-series available on diet of a seabird (spanning 34 years), we tested for changes in composition and the abundance of dominant prey species of this population. These observed changes were also compared with acoustic survey estimates of their biomass, and annual catch data. Since 1979, the prey composition has remained similar, but the dietary contribution of sardine and anchovy, which fluctuated inversely to each other, increased over the study period. These shifts seem to be reflective of fluctuations in the stock size of sardine and anchovy. Conversely, a third species, saury Scomberesox saurus, dominant in the non-breeding diet of the 1980s, decreased significantly in dietary abundance over the following two decades. It is likely that dietary shifts of Cape gannets at Bird Island were related to climate-mediated oceanographic change. The implications of such changes are discussed.